EFFECTIVENESS AND SAFETY OF PARENTERAL NUTRITION IN CRITICALLY ILL PATIENTS WITH INTRACRANIAL HEMORRHAGE - S. S. Petrikov; A. A. Solodov; E. V. Klychnikova; E. V. Tazina; M. A. Godkov; A. A. Ryk; V. V. Krylov (Неотложная медицинская помощь)
BACKGROUND The hypercatabolism syndrome may occur in critically ill patients after the intracranial hemorrhage. Mixed enteral and parenteral nutrition is used to provide nutrition support.MATERIAL AND METHODS We observed 20 patients with intracranial hemorrhage and consciousness score up to 13 (the Glasgow Coma Scale) in the early postoperative period.RESULTS Administration of parenteral mixture (“three-in-one”) was followed by the progressive growth of transferrin concentration and did not lead to the signifi cant increase of triglycerides concentration in the blood serum. We also noted that the parenteral nutrition lead to the increase of malonedialdehyde (MDA) in the blood serum above normal levels, but the total serum antioxidant activity was normal.CONCLUSION The 3-component mixture that contains polyunsaturated fatty acids omega 6/omega 3 — 2.5:1 and olive oil, administered to critically ill patients after intracranial hemorrhage, improves protein metabolism indicators and sustains lipid peroxidation and antioxidant activity in the blood serum.